Phytochemical and Antimicrobial Studies of The Crude Methanolic Extract of The Leaf of Cissus Cornifolia Baker (Planch) (Family: Vitaceae) - Atiku, I.; Musa, A. M.; Sani, Y. M; Hanwa, U.A; Abdullahi, S.M; Sule, M. I. (Asian Journal of Pharmaceutical Research and Development, 2013)
The antimicrobial activity of the crude methanolic extracts of the leaf of Cissus cornifolia were investigated using Cup-plate and agar Diffusion methods. The extract was tested against clinical isolates of Staphylococcus aureus, Streptococcus pneumoniae, Corynebacterium ulcerans, Pseudomonas fluorescence, Proteus vulgaris and Salmonella typhi. The extract showed activities against all the organisms tested (zone of inhibition: 20-26mm) with the exception of Corynebacterium ulcerans and Pseudomonas fluorescence. Phytochemical screening of methanol extract revealed the presence of flavonoids, steroids/triterpenes, tannins and saponins. This study showed that the leaves of Cissus cornifolia contains bioactive compounds with antimicrobial activity.